APLIKASI PEMBUATAN SERBUK JAHE INSTAN (Zingiber officinale R.) SEBAGAI MINUMAN PENINGKAT IMUN TUBUH DI KELURAHAN PURWODADI KABUPATEN BENGKULU UTARA - Intan Permata Sari; Ferry Lismanto Syaiful (Jurnal Hilirisasi IPTEKS, 2021)
Ginger is a type of rhizome that is found in fresh and processed form in Indonesia. Ginger has several benefits, one of which is to increase the body's immune system. The problem is that people still lack knowledge and expertise in processing ginger into products that have a long shelf life and are practical for consumption. The purpose of making ready-to-drink instant ginger powder is to create a practical, efficient, and durable product from the ginger plant. It is hoped that its health benefits will be obtained by increasing the body's immune system. This activity was carried out at the homes of residents of Purwodadi Argamakmur Village, North Bengkulu. The target of this activity is the women of Purwodadi Village to independently make this instant ginger for personal needs or use it as a business opportunity. Implementing this activity begins with the manufacture of instant ginger powder, which is then continued with a demonstration of making instant ginger powder to the people of Purwodadi Village. The results obtained in the socialization of making instant ginger powder in the form of increasing knowledge about how to make instant ginger powder and the health benefits of ginger. Meanwhile, there was an increase in community skills and expertise in making instant ginger powder for demonstration activities. It was concluded from the results of this activity that the resulting ginger products were distributed and socialized to the public and found public interest, especially mothers who were enthusiastic about gaining knowledge of the health benefits of ginger and how to make instant ginger powder. It is hoped that this activity will empower the women of the Purwodadi Village community so that they want to increase their family income and make instant ginger powder independently.